DESKRIPSI TINGKAT PENGETAHUAN IBU USIA PRODUKTIF TERHADAP IVA TEST DALAM DETEKSI DINI KANKER SERVIKS DI WILAYAH KERJA PUSKESMAS NAGRAK - Patimah, Papat; Septilia, Septilia; Hartati, Sri; Zahra, Alfina Putri; Yulianti, Inka (Jurnal Ilmiah Kesehatan Pernus, 2024)
Cervical cancer is a type of malignancy caused byHuman Papilloma Virus(HPV) is an oncogenic disease that attacks the cervix . Cervical cancer can be transmitted through sexual intercourse, so if someone has had sexual intercourse, it is recommended to carry out early detection. Cervical cancer most often occurs in women aged 15 to 49 years, and the risk of cervical cancer increases between the ages of 20 and 30 years (Information Center on HPV and Cancer (ICO), 2014. WHO predicts that in 2030 there will be a surge in cancer sufferers in Indonesia up to seven times. Every year, no less than 15,000 cases of cervical cancer occur in Indonesia. This makes cervical cancer the number one killer of women in Indonesia The highest number of cervical cancers in the world . The high morbidity and mortality rate of cervical cancer is caused by delays in treatment. Cervical cancer sufferers generally only come to health services after they are in an advanced stage, even though if they are detected as early as possible, cervical cancer can most likely be cured. can increase the life expectancy of women suffering from cervical cancer. The increasing incidence of cervical cancer occurs due to delays in early detection and lack of public knowledge about cervical cancer. The type of research used in this research is researchdescriptivewhich is carried out to determine the value of the independent variable, either one variable or more(independent)without making comparisons, or connecting one variable with another variable. Sampling is carried out “purposive sampling” namely a sampling technique with certain considerations.